LAMENTING LANGUAGE COURSES IN THE UNDERGRADUATE CURRICULUM - A Chaedar Alwasilah (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2010)
Pre-college education is mainly designed for character building, while college education is for profession building. However, on tertiary education levels students are still required to take mandatory subjects called Mata Kuliah Dasar Umum or General Education courses, whose function is to provide students with general knowledge—as opposed to specific knowledge or specialization—that will be useful for their career in the future. Students and professors are great admirers and promoters of their major or field of study, say English, but blind admiration may lead to myopic and prejudiced attitude. General education is created to counter fragmentation and specialization, which characterize advanced science and technology. General education, deliberately designed to facilitate inter-department interaction, will promote knowledge democratization among students.Among the problems faced by college students is the school college transition, namely a mismatch between faculty expectation and academic preparation of entering students. In most cases, the entering students lack the strong foundation for academic writing. This is telling enough that our basic education has failed to pave the way, namely basic literacy, for professional development. Indonesian as a general education course has been in the college curriculum since independence presumably to fix the mismatch.My survey on general education courses, however, shows that Indonesian is perceived the least important among the general education subjects. In other words, the Indonesian course has been a waste of time and energy. It is not an exaggeration, then, to hypothesize that university graduates in general lack the ability to express their ideas in academic writing in Indonesian, let alone in English. Many proposal submitted by faculty members are turn down simply because they do not know how write a good proposal. Reading their fellowship proposals, we could easily tell that their proposals lack convincing arguments.